Statistic D-Property of Voronoi Summation Methods of Class W_Q^2 - Dekanov, S. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We propose a general method for obtaining Tauberian theorems with remainder for one class of Voronoi summation methods for double sequences of elements of a locally convex, linear topological space. This method is a generalization of the Davydov method of C-points.